Konkurencyjność przedsiębiorstw sfery agrobiznesu przed integracją i po integracji z Unią Europejską : studium przypadków - Henisz-Matuszczak, Anna (Competitiveness of Agribusiness Firms Before and after Integration with the European Union : Case Study, 2006)
The main aim of this article is to show the competitive prevalence of the small agribusiness firms. The methods of the analysis is SWOT, while the subject is the group of four Wielkopolska's agribusiness companies, which were chosen with intent. The author identifies strength sides of firms and opportunities of its development, connecting it with properties of small firms' production, market's position, flexibility of scale's and kind of production to regional market's adaptation. These companies have to expect the limitation of its competitive prevalence, which could be a result of comparatively narrow assortment of available supply of agricultural staples, barriers of capital, high costs and distribution of employment and fiscal strain on its finances. The integration with the European Union changes competitive prevalence these firms. They can conditionally take advantage of market's enlargement and limited threats caused by appearance of competitive union companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 305-311